Pemberdayaan Kelompok Wanita Tani Mekar Rahayu Banjarnegara melalui Pelatihan Pembuatan Pestisida Nabati Daun Mindi - Eko Apriliyanto; Arum Asriyanti Suhastyo (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
Efforts to utilize garden land are expected to improve the family's economy by reducing spending on consumer vegetables. The obstacles faced in the use of home gardens are agricultural inputs in the form of fertilizers and pesticides, the use of which requires assistance. Fertilizer and pesticide products available around generally consist of synthetic chemicals. Excessive use of these two products can cause several negative impacts, one of which is residue on the harvest.  Therefore, it is necessary to use vegetable materials to make pesticides. The methods used were lectures, discussions, delivery of questionnaires, practice of making and applying mindi leaf vegetable pesticides. Participants experienced increased knowledge and skills in the manufacture and application of mindi leaf vegetable pesticides. The results of the correlation analysis between variables show that the correlation between education level and age is -0.3650. The correlation between education level and test scores is 0.6052. The correlation between age and test scores is -0.2206. The correlation between education level and age with test scores is -0.5240.